First Detection of Wolbachia in Namibian Bird Ectoparasites (Acariformes: Syringophilidae) with a Description of New Quill Mite Species - Eliza Glowska-Patyniak; Katarzyna Kaszewska-Gilas; Izabella Laniecka; Julia Olechnowicz; Kamila Ostrowska; Wiktoria Dmuchowska; Brian K. Schmidt; Jan Hubert; Artur Trzebny (Animals)
Wolbachia is a common intracellular bacterial genus that infects numerous arthropods and filarial nematodes. In arthropods, it typically acts as a reproductive parasite, leading to various phenotypic effects such as cytoplasmic incompatibility, parthenogenesis, feminization, or male-killing. Quill mites (Acariformes: Syringophilidae) are a group of bird parasites that have recently attracted increasing interest due to the detection of unique phylogenetic lineages of endosymbiotic bacteria and potentially pathogenic taxa. Our study used an unbiased 16S rRNA gene amplicon sequencing approach to examine several populations of Namibian quill mites for the presence of bacteria that could affect their biology. We detected Wolbachia in two mite populations collected from two species of larks. However, we did not find any other endosymbiotic bacteria or any that could be of epidemiological importance. Since the mite taxa we tested were previously unknown to science, we conducted comprehensive morphological and molecular systematic analyses on them. Our research revealed two new quill mite species of the genus Syringophilopsis Kethley, 1970 which parasitize three sub-Saharan alaudids, i.e., Syringophilopsis erythrochlamys sp. n. from the dune lark Calendulauda erythrochlamys (Strickland, HE) and S. christinae sp. n. from the Karoo long-billed lark Certhilauda subcoronata (Smith) and spike-heeled lark Chersomanes albofasciata (de Lafresnaye, NFAA). In addition, we provided the African reed warbler Acrocephalus baeticatus (Vieillot, LJP) as a new host for S. acrocephali Skoracki, 1999. Our study expands the knowledge on parasite diversity and provides new insights into Wolbachia infection among quill mites in Africa.